Pre-departure policies for migrants' origin countries - Toman Barsbai (Kiel Institute for the World Economy (IfW), Poverty Reduction, Equity and Growth Network (PEGNet), 2018)
International migration generates large benefits for migrants and their family members who stay behind. But migrants' socio-economic integration in destination countries is often imperfect and many migrants face the risk of exploitation. Migrants' origin countries should therefore consider policies to increase the benefits of international migration. Pre-departure orientation seminars for migrants and financial education can improve migrant's decision-making. Likewise, behavioral interventions can reduce migrant mistreatment. These policy options are low-cost and have shown promising impact in the contexts they were evaluated. It may pay off to experiment with them in other contexts.
Keywords: 330